Explaining monetary policy in press conferences - Michael Ehrmann; Marcel Fratzscher (European Central Bank (ECB), 2007)
The question how best to communicate monetary policy decisions remains a highly topical issue among central banks. Focusing on the experience of the European Central Bank, this paper studies how explanations of monetary policy decisions at press conferences are perceived by financial markets. The empirical findings show that ECB press conferences provide substantial additional information to financial markets beyond that contained in the monetary policy decisions, and that the information content is closely linked to the characteristics of the decisions. Press conferences indeed have on average had larger effects on financial markets than even the corresponding policy decisions, and with lower effects on volatility. Moreover, the Q&A part of the press conference fulfils a clarification role about the economic outlook, in particular during periods of large macroeconomic uncertainty.
Keywords: E52; E58; G14; 330; communication; European Central Bank; financial markets; monetary policy; press conference; real-time analysis; Geldpolitik; Zentralbank; Öffentlichkeitsarbeit